1994
DOI: 10.1111/j.1432-1033.1994.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure elucidation and biosynthesis of 31‐methylhopanoids from Acetobacter europaeus

Abstract: Apart from a nuxture of bacteriohopanetetrols already found in other Acetobacter species, four new 3P-methylhopanoids have been isolated from Acetobacter europaeus. All of them present an ether linkage between a bacteriohopanetetrol or a bacteriohopanepentol and a carbapseudopentose moiety often found in bacterial hopanoids. Three of these ethers were shown by comparison with synthetic reference hopanoids to posess a supplementary methyl group at C31. This novel series of methylhopanoids may be the precursor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 19 publications
3
27
0
Order By: Relevance
“…In the preliminary paper we proposed a series of ions which should be characteristic of pentafunctionalised components other than those with an amino group at C‐35 ( m/z 713, 653, 593, 533 and 473) 4. Currently, the best‐known bacterial sources of composite pentafunctionalised BHPs are the cyanobacteria,10 although they have also been observed in nitrogen‐fixing bacteria11 and acetic acid bacteria 12. Accordingly, we screened a number of cyanobacterial cultures for the presence of pentafunctionalised components (H. M. Talbot, R. Summons, L. Jahnke, P. Farrimond, unpublished results).…”
Section: Resultsmentioning
confidence: 99%
“…In the preliminary paper we proposed a series of ions which should be characteristic of pentafunctionalised components other than those with an amino group at C‐35 ( m/z 713, 653, 593, 533 and 473) 4. Currently, the best‐known bacterial sources of composite pentafunctionalised BHPs are the cyanobacteria,10 although they have also been observed in nitrogen‐fixing bacteria11 and acetic acid bacteria 12. Accordingly, we screened a number of cyanobacterial cultures for the presence of pentafunctionalised components (H. M. Talbot, R. Summons, L. Jahnke, P. Farrimond, unpublished results).…”
Section: Resultsmentioning
confidence: 99%
“…Trace amounts of a ring-monounsaturated bishomohopanol -most likely a product from the cleavage of vicinal diols of the unsaturated aminotriol -were also found. High fragments with m/z 367, 189 and especially 334, 307 and 217 after GC/MS of the TMSderivative indicated the double bond position of the bishomohopenol at D11 (see also Simonin et al, 1994, who reported respective fragments for the acetate derivative of D11 hopenols). However, due to the lack of reference compounds, the uncertainties from the GC/MS identification, and the coelution of the unsaturated aminotriol with other components during LC-MS analyses, we were not able to unambiguously identify the double bond position of the unsaturated aminotriol.…”
Section: Free and Bound Bacteriohopanepolyols (Bhps)mentioning
confidence: 93%
“…2␤-MethylBHPs occur in many hopanoid-producing cyanobacteria, for which they seem to be good marker compounds , although 2-methylhopanoids lacking the C 5 side chain (i.e., 2␤-methyldiploptene and/or 2␤-methyldiplopterol) have been found in a Type II methanotrophic bacterium (Methylobacterium organophilum; Renoux and Rohmer, 1985) and in three nitrogen-fixing bacteria (Vilchèze et al, 1994;Bravo et al, 2001). 3␤-MethylBHPs are absent from these bacteria, but have been reported in many Type I methanotrophs (Neunlist and Rohmer, 1985;Cvejic et al, 2000), and in some acetic acid bacteria (Simonin et al, 1994). Type I and II methanotrophic bacteria are phylogenetically distinct groups of methane-oxidizing bacteria that tend to predominate in different environments; Type I methanotrophs are dominant at low methane concentrations, such as in aquatic environments, with Type II methanotrophs generally being favored in soils and ground waters (Hanson and Hanson, 1996).…”
Section: Introductionmentioning
confidence: 97%